Possible applications for a digital ground model in infrastructure construction. Issue 5 (1st October 2021) - Gächter, Werner; Exenberger, Hans; Fasching, Alfred; Hillisch, Stefan; Mulitzer, Günther; Seywald, Martin; Rettenbacher, Martin; Fleischmann, Gregor; Fröch, Georg; Flora, Matthias
Abstract: Das BIM‐Pilotprojekt „Neubaustrecke Köstendorf‐Salzburg" der ÖBB‐Infrastruktur AG umfasst eine ca. 21 km lange zweigleisige Neubaustrecke mit einer Vielzahl unterschiedlicher Ingenieurbauwerke und intensiver multidisziplinärer Abstimmungsnotwendigkeit in einem sensiblen Projektraum. Die Zielvorgabe einer weitgehend softwareunabhängigen Gesamtmodellierung mit Überführung der gewonnenen Erkenntnisse in die Auftraggeber Informations Anforderungen bzw. nachfolgend einen BIM‐Abwicklungsplan konnte erfolgreich abgeschlossen werden. Neben internen Abstimmungen erfolgte eine erste externe Abstimmung über die im Rahmen eines Genehmigungsverfahrens für eine Behörde erforderlichen Modellinhalte sowie deren Verfügbarkeit mittels direktem Modellzugriff. Durch die integrale und kollaborative Projektbearbeitung war es möglich, umfangreiche, auf die Bedürfnisse der jeweiligen Projektpartner abgestimmte Abläufe für die einzelnen Fachmodelle zu definieren und zu einem Gesamtmodell zu koordinieren. Das Ergebnis des koordinierten Gesamtmodells zeigt u. a. die umfassenden Möglichkeiten eines parametrisierten Baugrundmodells in der transparenten Risiko‐ und Projektbeurteilung und weist den Weg hin zum holistischen, phasenorientierten Infrastruktur Informationsmodell. Dabei ist es aus Sicht der Autoren wichtig, die erprobten internen Arbeitsabläufe der Projektpartner nur minimal zu adaptieren und in BIM‐taugliche, kooperative Workflows zu überführen. Abstract: The BIM pilot project "New Köstendorf‐Salzburg Line" for ÖBB‐Infrastruktur AG covers a new twin‐track section about 21 km long involving a wide variety of different engineering structures and a corresponding need for close interdisciplinary collaboration within a sensitive project space. The pilot project successfully achieved its objective of generating a largely software‐independent overall model and transferring the knowledge gained to the Employer's Information Requirements and subsequently to a BIM execution plan. In addition to internal coordination meetings, a preliminary external meeting took place to discuss the model elements required for a government agency as part of an approval process and the availability of such elements by means of direct access to the model. By adopting an integrated, collaborative approach to project management, it was possible to define extensive procedures and workflows adapted to the needs of the respective project partners for the single‐discipline models (specialist models) and to coordinate an overall federated model. The results of the co‐ordinated overall model show the ample opportunities afforded by a parameterised ground model for transparent risk and project assessment, paving the way for a holistic, phase‐based infrastructure information model. In this regard, the authors felt that it was important to adapt the project partners' established internal procedures only minimally and to translate them into BIM‐compatible, cooperative workflows.